Multiple Neural Networks Malfunction in Primary Blepharospasm: An Independent Components Analysis - Huang, Xiao-Feng; Zhu, Meng-Ru; Shan, Ping; Pei, Chen-Hui; Liang, Zhan-Hua; Zhou, Hui-Ling; Ni, Ming-Fei; Miao, Yan-Wei; Xu, Guo-Qing; Zhang, Bing-Wei; Luo, Ya-Yin (Frontiers in Human Neuroscience, 2017)
Primary blepharospasm (BPS) is a focal dystonia characterized by involuntary blinking and eyelid spasms. The pathophysiology of BPS remains unclear. Several neuroimaging studies have suggested dysfunction of sensory processing and sensorimotor integration, but the results have been inconsistent. This study aimed to determine whether patients with BPS exhibit altered functional brain connectivity and to explore possible correlations between these networks and clinical variables. Twenty-five patients with BPS and 25 healthy controls were enrolled. We found that the patient group exhibited decreased connectivity within the sensory-motor network, which involved regions of the bilateral primary sensorimotor cortex, supplementary motor area, right premotor cortex, bilateral precuneus and left superior parietal cortex. Within the right fronto-parietal network, decreased connections were observed in the middle frontal gyrus, dorsal lateral prefrontal cortex and inferior frontal gyrus. Regarding the salience network, increased connectivity was observed in the left superior frontal gyrus and middle frontal gyrus. These findings suggest the involvement of multiple neural networks in primary blepharospasm.